Depiction of Bhairava in a dancing posture - Temples of India Project Team (Jio Institute, 2024)
Bhairava is portrayed dancing, his four arms moving in a divine rhythm. Notably, Bhairava wears unique footwear with a distinct heel. His left foot, adorned with a sandal, rests firmly on the ground, while his right foot is raised inward, adding dynamism to his celestial dance. In his upper hands, Bhairava holds a damru (drum) and a bowl. His lower left hand holds a severed human head, while his lower right hand grasps an object resembling a musala (pestle). His appearance is marked by a highly raised hairstyle, a moustache, and a flowing beard.